EVALUASI KINERJA PEGAWAI DENGAN METODE CHECK LIST DI PT XYZ - Fajri Sodik; Nur Syamsudin; Syamsul Hidayat (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This research aims to improve the performance of PT XYZ employees based on an assessment of the understanding of work standards, work instructions, use of personal protective equipment (PPE), implementation of 6S and 3M, work reporting, overtime readiness, work motivation, and work responsibilities. This study was conducted at PT XYZ in December 2024 using a quantitative approach with data collected from 10 assembly operators through observation and performance assessment using a scale of 1-4. The results of the analysis showed that 100% of operators had high performance.